The Role of ChatGPT in Enhancing Academic Performance at University Level: Opportunities, Challenges, and Ethical Implications - Rawal, Shankar Bahadur (AMC Multidisciplinary Research Journal, 2025)
The rapid advancement of artificial intelligence (AI), especially tools like ChatGPT, is revolutionizing the education sector by providing new opportunities to enhance academic performance and digital literacy. This study explores the role of ChatGPT in improving academic outcomes of university students. Synthesis review approach was used, involving a comprehensive literature review to assess the applications, benefits, and challenges of using ChatGPT in higher education. The research process included reviewing academic articles, policy documents, and case studies related to AI tools in education. Findings indicate that ChatGPT offers substantial support in writing, research, and problem-solving, helping students overcome barriers like language proficiency and limited resources. It also plays a crucial role in enhancing digital literacy, as students interact with AI to develop skills that are increasingly vital in today's technological landscape. However, the study highlights several challenges, including the risk of over-reliance on AI-generated content, academic dishonesty, and ethical concerns surrounding plagiarism and misinformation. The study emphasizes that while ChatGPT can foster engagement and academic success, its integration requires careful consideration. The implications call for universities in Nepal to adopt clear policies on AI usage, implement AI literacy programs, and raise awareness of academic integrity. Responsible AI integration is crucial to ensure that students benefit from these technological advancements while maintaining academic rigor. This research contributes valuable insights into how ChatGPT can be effectively used in higher education, balancing its opportunities with the ethical responsibilities of academic institutions.